Sterilization effects on the physical properties and cytotoxicity of poly (glycerol sebacate) - Rai, Ranjana; Tallawi, Marwa; Roether, Judith; Detsch, Rainer; Barbani, Niccoletta; Rosellini, Elisabeth; Kaschta, Joachim; Schubert, Dirk W.; Boccaccini, Aldo R. (Materials Letters, 2013)
The influence of conventional sterilization methods such as gamma irradiation, ethylene oxide treatment and steam exposure on the physical properties of poly(glycerol sebacate) (PGS) was investigated. Scanning electron microscope (SEM) observations, attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) and Raman spectra demonstrated that the applied sterilization methods do not induce adverse surface modifications. The sterilized samples also maintained their thermal and mechanical properties post-sterilization. In addition, gamma sterilized PGS films did not induce any toxicity when films were in contact with murine fibroblast 313 cells. PGS is compatible for all the sterilization methods used in this study, which is of relevance for the wider application of PGS in medical devices. (C) 2013 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.steril
Keywords: Biocompatibility; Biopolymers; Gamma irradiation; Poly(glycerol sebacate); Sterilization